(untitled) (Al-Qamar, 2020)
This article presents an overview of Fehmīda Riāz’s concept of Women’s rights in the light of Islamic teachings. Fehmīda Riāz may not have considered Islamic teachings to be flawed in terms of women’s rights, but her study of eastern was that of those who believed in Islamic beliefs, but were far from the practical form of the Islamic social system. History has shown that it is the so-called Muslims who have brought Islam into disrepute, who have only embraced the Islamic system of worship, while ignoring other aspects. However a reader sees Fehmīda Riāz as far from moderate in this regard, which may lead to the conclusion that under the guise of women’s rights, men’s rights appear to be affected, and in the light of Islamic teachings, men’s denial is often an essential part of this thinking. As the Quran and Sunnah insist that a woman’s existence will be protected as long as she is inside the house, Fehmīda Riāz insists on pulling her out, which is an unmediated attitude. Veil and modesty is an important and fundamental subject of Islam, the details of which are clear in the Quran and Ḥadīth, as well as the aspect of establishing peace and order in Islamic society in terms of mutual relations. The way in which women are portrayed in Fehmīda’s fictions and novels, Islamic values ​​are not ready to accept even for a moment. Fehmīda’s influence by the West cannot be denied, but her sincerity and deafness to Islamic teachings do not go unnoticed. In fact, Fehmīda’s seems to be a representative of the particular class, who are imitators of feminist rights in Europe, while the majority of Pakistani society tends to be Islamist and traditionalist. That is why Fehmīda and her ideas are being severely criticized.